2019
DOI: 10.1097/md.0000000000014642
|View full text |Cite
|
Sign up to set email alerts
|

Ectopic papilla of Vater in duodenum bulb

Abstract: The major papilla of Vater can be ectopically present in the stomach, pyloric canal, duodenal bulb, and third or fourth portion of the duodenum. In this study, we determined the clinical significance of ectopic papilla of Vater by endoscopic retrograde cholangiopancreatogram (ERCP). A retrospective study was conducted by reviewing the medical records of 6133 patients receiving ERCP from 1988 to 2011. The diagnosis was confirmed if both the common bile duct (CBD) and the main pancreatic duct (PD) dra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 18 publications
2
15
0
Order By: Relevance
“…Ectopic papilla of Vater is an underdiagnosed disease, and anomalous termination in the stomach is rare[ 2 , 4 ]. A retrospective study with 6133 enrollees who had received ERCP in Taiwan between 1988 and 2010 reported an incidence of approximately 0.13%, corresponding to the prevalence rate of Taiwan’s general population[ 2 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Ectopic papilla of Vater is an underdiagnosed disease, and anomalous termination in the stomach is rare[ 2 , 4 ]. A retrospective study with 6133 enrollees who had received ERCP in Taiwan between 1988 and 2010 reported an incidence of approximately 0.13%, corresponding to the prevalence rate of Taiwan’s general population[ 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…Diagnosis is dependent on the observation of the orifice location and duct through radiographic visualization with contrast medium[ 2 , 8 ]. Recognizing an ectopic papilla of Vater and ruling out fistulas, which may be secondary to ulcer diseases or choledocho-lithiasis, spontaneous or iatrogenic surgical fistulas, or surgical choledochoenteric diversions are also crucial[ 9 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One such feature is duodenal ulcer. Lee et al [ 4 ] and Taş et al [ 18 ] reported that 13 out of 18 patients (72%) and 16 out of 20 patients (80%) had a history of duodenal ulcers, respectively. Duodenal ulcers may be associated with apical stenosis or deformity.…”
Section: Discussionmentioning
confidence: 99%